A survey of parent experience in a specialist paediatric epilepsy outpatient clinic. (24th May 2012) - Madhu, R; McTague, A; Iyer, A; Appleton, R
Abstract : Aim: To assess the outpatient clinic experience of children with epilepsy and their families under the care of one paediatric neurologist attending a single specialist epilepsy clinic. Methods: The survey was undertaken prospectively over 12 months. Families of both new and follow-up patients who attended the clinic were provided with a simple standard questionnaire with eight questions addressing staff courtesy, communication, clinic visits and their overall experience. Each family was requested to anonymously complete only one questionnaire during the audit period irrespective of how many times the child was seen during the 12 months. All children were seen by the same consultant or specialist registrar in paediatric neurology. Data were analysed by the Trust's Audit Department. Results: Two hundred and thirty eight (238) questionnaires were given of which 229 (96.2%) were returned. All were completed anonymously. Courtesy: 100% (229/229) of families reported that the reception, nursing and medical staff were friendly and polite. Communication: 100% (229/229) reported that the doctors were easy to talk to and their questions were listened to and adequately answered. 97.4% (223/229) stated that they received enough information about epilepsy during the visit; two replied that this was inadequate. 98.7% (226/229) replied that their child's epilepsy had been clearly explained. Clinic visits: 97.4% (223/229) felt that waiting times were acceptable. 90% (206/229) replied that the frequency of clinic visits was appropriate whilst 7 (3.1%) said they were too infrequent. 92% (211/229) considered that they spent the right amount of time with the doctor. 99.6% (228/229) stated that the clinic visit was useful. Overall impressions: 100% (229/229) reported they were happy with their child's care received during the clinic visit. Conclusion: This survey has demonstrated that the vast majority of families found the entire epilepsy clinic experience positive and supportive and were satisfied with the experience. There is little published information on family experience of an entire clinic journey. The results of this survey compares very favourably with two earlier studies undertaken in much smaller populations in a District General Hospital.